The popularity of Biden and Trump in the United States and Latin America during the 2020 campaign: A study through Google Trends - Cerdán-Martínez, Víctor; Bárcena, Sergio; Villa-García, Daniel (VISUAL REVIEW. International Visual Culture Review / Revista Internacional de Cultura Visual, 2024)
Donald Trump and Joe Biden disputed an atypical electoral campaign marked by the Covid-19 pandemic and high impact social and racial conflicts. Even though, there are several articles that have studied the determining factors of the democrat leader’s victory, none has analyzed the effects of the electoral campaign on the internet. This article renders an analysis on Trump’s and Biden’s popularities and their evolution on Google and YouTube during the 2020 presidential campaign in the United Stated and a few Latin American countries: Brazil, Mexico, Colombia, Argentina, Peru, Venezuela and Chile.